DEVELOPMENT OF A SET OF REQUIREMENTS FOR THE DESIGN OF COMFORTABLE CLOTHING FOR YOUNG CHILDREN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
For moral satisfaction, clothing should correspond to aesthetic preferences, which will vary depending on the age group of children, which is associated with psychological crises. It should be noted that the concept of "comfort" is complex and reflects the state of comfort of the body from a subjective point of view, which is based on a sense of satisfaction when using clothes.